Anti-Matters: Mortal Ethics in Cormac McCarthy’s The Road - Patrick Damien O’Connor (European Journal of American Studies, 2017)
This article proposes that to understand the ethical and philosophical dimensions of Cormac McCarthy’s work one must engage in an articulation of mortal ethics. To do this, it is necessary to understand how The Road depicts the material destruction of the world, and the ethical consequences such physical destruction imposes on the novel’s central protagonists. More specifically, this article argues that Cormac McCarthy’s The Road presents an anti-metaphysics with consequences for understanding philosophical concepts of memory and community, as well as McCarthy’s effort to construct universal forms of being together.